1990
DOI: 10.1080/00102209008951628
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Evaluation of the Onboard Decomposed Methanol Spark-Ignition Engine

Abstract: The possibility of obtaining high efficiency and low emissions of hazardous compounds by using decomposed methanol, i.e., hydrogen and carbon monoxide, as a fuel for spark-ignition engines has been investigated theoretically and experimentally. A cycle simulation predicts that the most important advantage with the system is the opportunity to run the engine on lean air/fuel mixtures.In the experiments, bottled gas was used instead of gas from a decomposition reactor. The results indicate that the efficiency ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…5%) is mixed with syngas in the synthesis of methanol. 9 By the reverse reaction of MeOH synthesis, viz., methanol decomposition, 66 syngas can be obtained in situ. For small-scale applications of syngas this often is a convenient route.…”
Section: Conversion To Products Via Syngasmentioning
confidence: 99%
“…5%) is mixed with syngas in the synthesis of methanol. 9 By the reverse reaction of MeOH synthesis, viz., methanol decomposition, 66 syngas can be obtained in situ. For small-scale applications of syngas this often is a convenient route.…”
Section: Conversion To Products Via Syngasmentioning
confidence: 99%
“…The change in the MER explained for a small improvement in engine efficiency with the dissociated methanol compared to the neat methanol at λ close to 1 [19]. A bigger difference in the efficiency can be seen at a highly diluted condition (lean burn or EGR dilution), as in [20,21]. 40%.…”
Section: Idealized Efficiencymentioning
confidence: 94%
“…However, the enhancement was small (3-7%) if it was compared to the efficiency that could be obtained with an engine operated on pure methanol, which itself is smaller than the change in LHV of dissociated methanol [19]. Work was also done on decomposed methanol at lean conditions, and showed a significant improvement in efficiency compared to neat methanol [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…During the 1980s–1990s, some studies about the use of decomposed methanol as a fuel for SI engines were done at the Royal Institute of Technology–KTH. They concluded that the engine could start at −30 °C and the engine efficiency increases by 15%–20%, relative to neat methanol, with the presence of hydrogen-rich gas (syngas). Brinkman and Stebar performed an experimental study to compare the engine efficiency and fuel consumption with methanol and decomposed methanol at a varied compression ratio and equivalence ratio. At the same compression ratio and equivalence ratio, although the LHV increased by ∼13%, the reduction of fuel consumption for decomposed methanol was ∼3%–7%, compared to methanol.…”
Section: Introductionmentioning
confidence: 99%